Recent advances of the ultimate microbial influenced corrosion (MIC): A review - Albarqouni, Yasin M.Y.; Ali, Gomaa A. M.; Chong, Kwok Feng; Nurul Huda, Abu Bakar; Althubaiti, Randa; Arman, Abdullah (Bentham Science, 2024)
The persistent corrosion of metal surfaces poses a significant engineering challenge, including material degradation, loss of metal-structural integrity, and massive maintenance costs in various industrial, medical, and aerospace applications. Microorganisms such as archaea, bacteria, fungi, and microalgae can directly or indirectly influence metal corrosion. The degree of corrosiveness and corrosion healing varies depending on the microbe, medium, and metal substrate characteristics. Several attempts have been made to reveal answers to all questions about MIC. The published reports focused on testimonial failures and laboratory or field tests under varied situations. This review offers an overview of the most recent MIC research and emphasizes the scarcity of data on MIC detection, estimation, and the most recent approaches for MIC management. The review extends previously reported works and summarizes efforts for better understanding and cutting off MIC management in advanced technologies. Furthermore, it concludes with a final discussion of the current and future drawbacks and protective systems for preventing microbial-induced corrosion.